Taṭwīr Ta`līm al-Imlā’ al-Manqūl Bi Rabṭ al-Ḥurūf `Alā Asās Madkhal Learning Together Wa Ṭarīqah Scramble Bi MTsN 4 Aceh Selatan - Liyudza Rahayu; Buhori Muslim; Badruzzaman Badruzzaman (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2023)
Based on observations in class one (1) MTsN 4 Aceh Selatan. The researcher found that some students had problems, they had difficulty writing. As well as the difficulties faced by students regarding spelling, use of punctuation marks, choosing vocabulary, and constructing sentences. To overcome this problem, the researchers developed learning Imla' Manqul with rabthil letters based on the Learning Together approach and the Scramble method at MTsN 4 Aceh Selatan. The purpose of this study was to identify student responses in the development of learning Imla' Manqul with rabthil letters based on the Learning Together approach and the Scramble method at MTsN 4 Aceh Selatan. The research method used by researchers is a scientific research and development method using the One Group Pre-Test and Post-Test Design. To collect data, researchers use tests and questionnaires. The results of this study are learning Imla' Manqul with rabthil letters based on the Learning Together approach and the Scramble method is effective at MTsN 4 Aceh Selatan. Based on the results (t-test), which is 14.67, it is greater than the results (t-table), which is 2.06. Results of student respondents on the development of learning Imla' Manqul with rabthil letters based on the Learning Together approach and the Scramble method at MTsN 4 Aceh Selatan. with a score of 94%, with a very good.